THE EFFECT OF PREVIEWING TEXT ON FRESHMEN READING COMPREHENSION SKILL - Putri Saniatul Iklima; Muhammad Yunus; Fitri Awaliyatush Sholihah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: EFL students have several problems in understanding English texts. These issues are shown when the students have no idea with unfamiliar vocabularies and the concepts of the text. Previewing a text can be used for stimulating prior knowledge. These activities can be practiced to increase the accuracy and efficiency of students reading. This research used quantitative research; quasi experimental design. There were 52 first year students as the research participants and divided into control and experimental group. The treatment given was providing preview text of “Birth of Blues” which consisted of 372 words, while the control group were given the same passage without preview text. The writer provided an objective test to measure the students’ comprehension toward the text. The result showed that the mean of control group was (M=52.31) and the mean of experimental group was (M= 67.69). In the same case, the p value was 0.000 (p < 0.05). After knowing the result of the data, it indicated that providing preview text strongly affected freshmen’s reading comprehension. In conclusion, the more the students can do previewing before reading the text, the more they can understand the whole text easily and they will achieve better reading skill. Keywords: Preview, reading, comprehension